The Comparative Law Study: E-Commerce Regulation in Indonesia and Singapore - Moha, Mohamad Rivaldi; Ahmad, Ahmad; Harun, Amanda Adelina; Elfikri, Nurul Fazri (Universitas Negeri Gorontalo, 2023)
Indonesia and Singapore were the founding members of an economic and geopolitical organization of countries in the Southeast Asian region called the Association of Southeast Asian Nations (ASEAN). ASEAN mandates each member country to create regulations and policies related to e-commerce transactions through the 1999 ASEAN Summit. This paper is a normative study and aims to analyse the development of e-commerce regulations in Indonesia and Singapore by utilizing comparative and statute approaches. The result of the study finds out that Singapore has designed its e-commerce master plan since 1998, meanwhile, Indonesia started to develop the master plan related to e-commerce a decade late than Singapore through the Acceleration and Expansion of Indonesian Economic Development program (MP3EI), which launched in 2011. Indonesia has regulated a few components related to e-commerce, but some are still partial and spread in a few regulations. This paper recommends governments unify all e-commerce components regulations into one act that can cover legal protection and become the basis of procedure regulation related to e-commerce in Indonesia. The usage of the Trustmark stamp and online registration procedure for the e-commerce activities required by Singapore can be enforced in Indonesia as a solution to problems that occur in e-commerce activity in Indonesia.